Nitrate risk assessment in drinking water in different areas of Malayer city - Eisa Solgi; Fouzieh Beigmohammadi; Raziyeh Ahmadvand; Sara Baser (رویکردهای نوین در مهندسی آب و محیط زیست)
Objective:In the present study, the quality of drinking water resources of Malayer city was evaluated using Wilcox,WQI and NPI indices and the non-carcinogenic risk caused by nitrates in drinking water. Methods:For this purpose, 60 tap water samples were taken from 15 urban areas and pH, EC and NO3 were measured in each sample. After determining water quality with the help of indicators and comparing the values of these parameters with the WHO standard and the national standard of Iran;The amount of daily intake(CDI) of nitrate and non-carcinogenic risk(HQ) in four age groups of infants, children, adolescents and adults were calculated for different areas of Malayer city.Results: Based on the obtained results, the quality of urban drinking water sources of Malayer was evaluated as excellent and without pollution. The average pH,EC and nitrate were 7.42, (µS/cm) 710.49 and(mg/L) 6.09, respectively, in the case of pH and nitrate, these values were below the permissible limit and for electrical conductivity, they were above the permissible limit. the desired standards.The non-carcinogenic risk was estimated to be less than one in all regions, and its value was obtained from the highest to the lowest,respectively,for infants, children, adolescents, and adults. So that the highest daily absorption of nitrate was estimated to be 0.443 mg/kg body weight per day for infants and the lowest(mg/kg/day) was 0.041 mg/kg/day for adults.Conclusions:Based on this, infants are the most vulnerable group to nitrate pollution. The non-carcinogenic risk of nitrates was the lowest in Fakhriyeh and the highest in valiasr.